GERAKAN RESISTENSI TERHADAP PERDA NO. 2 TAHUN 2016 TENTANG PARIWISATA HALAL OLEH KELOMPOK ABU SHOFA DI DESA SEMBALUN LAWANG LOMBOK TIMUR 2018-2021 - Kurniawan, Hendri; Erawan, Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
This study examines the rejection and resistance movements carried out by religious-based groups against the application of halal tourism in Sembalun Lawang Village, East Lombok in the period 2018 to 2021. The theory used in this study is the resistance theory of James C. Scott and the theory of Islamic populism Vedi R. Hadiz. The results of this study indicate that the form of hidden transcripts carried out by pro-tourism groups and contra-tourism groups both depart from sentiment towards other groups, which then creates gossip and becomes an internal discourse in each group. Then Saturnalia, which became a connecting factor for the emergence of conflict, was the 2018 earthquake. Then the public transcript of the two groups was in the form of open conflict, destruction and closing of tourism destinations.   Keywords: Hidden Transcript, Islamic Populism, Public Transcript, Saturnalia